Pentoxifylline or theophylline use in hospitalized COVID‐19 patients requiring oxygen support - Wall, Geoffrey C. (Clin Respir J, 2021)
INTRODUCTION: The phosphodiesterase inhibitors theophylline and pentoxifylline have anti‐inflammatory properties that may make them useful in COVID‐19 pneumonia. We conducted a retrospective review of hospitalized COVID‐19 patients requiring oxygen who received these drugs. OBJECTIVES: To examine the potential efficacy and safety of theophylline and pentoxifylline in COVID‐19 pneumonia patients. METHODS: Adults with a positive test for SARS‐COV2 and were hospitalized due to pneumonia requiring either high flow nasal cannula or mechanical ventilation were included. Patients with a history of asthma or chronic obstructive pulmonary disease were preferentially given theophylline. All other patients received pentoxifylline 400 mg orally TID. A group of hospitalized COVID‐19 patients receiving standard of care acted as a comparison group. The coprimary outcomes were a change in C‐reactive protein (CRP) and ROX score between groups from day 1 to day 4 of therapy. RESULTS: Two hundred and nine inpatients were reviewed. Fifty‐eight patients received pentoxifylline/theophylline, with 151 patients serving as the comparison group. Active therapy was associated with an increase in the ROX score (mean: 2.9 (95% CI: 0.6, 5.1)) and decrease in CRP (mean: −0.7 (95% CI: −4.7, 3.2). Mortality rates were theophylline/pentoxifylline 24% and comparison group had a 26%, respectively. CONCLUSION: In this retrospective study, theophylline and pentoxifylline were associated with an increase in ROX score and nominal decreases in CRP and mortality. Treatment was safe with few adverse reactions documented. We believe that this study could the basis for randomized‐controlled trials to further explore these drugs’ role in COVID‐19.